Unsteady MHD Free Convective Flow Past an Inclined Parabolic Accelerated Plate with Hall Current, Radiation Effects and Variable Temperature in a Porous Medium - Nalisi, Gilbert Magiboi; Okello, Jeconia Abongo; Sigey, Johana Kibet; Kimathi, Mark Erick Mwiti (International Journal of Management and Fuzzy Systems, 2017)
We analyze the effects of hall current and radiation on unsteady hydromagnetic free convection flow of a viscous incompressible electrically conducting fluid past an inclined parabolic accelerated plate in a porous medium by applying a transverse magnetic field which makes an angle to the inclined plate.The fluid is assumed to be viscous, incompressible and electrically conducting with a strong magnetic field. Using the modified Ohm’s law and the Bossinesq approximation the governing equations of the problem are reduced to local non-similarity boundary layer equations using suitable transformation.The dimensionless governing equations of flow field are solved numerically by Crank-Nicolson finite difference method for different values of governing flow parameters. The velocity and temperature profiles are shown through graphs.
Keywords: MHD Free Convection Flows, Heat Transfe; Hall Currents; Radiation; Transverse Magnetic Field; Inclined Parabolic Accelerated Plate; Porous Medium